2017
DOI: 10.21470/1678-9741-2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Liver Injury with Papaverine and Ascorbic Acid Due to Infrarenal Cross-Clamping: an Experimental Study

Abstract: ObjectiveIschemia-reperfusion injury after acute ischemia treatment is a serious condition with high mortality and morbidity. Ischemia-reperfusion injury may result in organ failure particularly in kidney, lung, liver, and heart. In our study, we investigated the effects of papaverine and vitamin C on ischemia-reperfusion injury developed in the rat liver after occlusion-reperfusion of rat aorta.Methods32 Sprague-Dawley female rats were randomized into four groups (n=8). Ischemia was induced with infrarenal ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(27 reference statements)
0
7
0
2
Order By: Relevance
“…[ 1,29 ] Hüseyin et al reported vacuolization in hepatocytes, parenchymal necrosis, and vascular congestion. [ 30 ] Santos et al reported widespread edematous areas and vascular congestion due to aortic I/R. Those authors also reported moderate inflammation in hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,29 ] Hüseyin et al reported vacuolization in hepatocytes, parenchymal necrosis, and vascular congestion. [ 30 ] Santos et al reported widespread edematous areas and vascular congestion due to aortic I/R. Those authors also reported moderate inflammation in hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Although the tissue damage mechanism has not been fully explained in I/R studies based on clamping the infra‐renal aorta, increasing free oxygen radical production resulting from lipid peroxidation has been reported to lead to oxidative stress. [ 7,9,30 ] Şener et al reported an increase in liver tissue MDA levels, while GSH levels decreased, following I/R of the infrarenal aorta. [ 33 ] We also observed elevated MDA levels and decreased GSH levels in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Bunlar içerisinde vitaminler eksojen antioksidanlar grubunda yer alır. Vitaminlerin deneysel kalp iskemi reperfüzyon modellerinde antioksidan özelliğini kanıtlayan pek çok başarılı çalışma mevcuttur 8,9 .…”
Section: İskemi-reperfüzyonunclassified
“…Bu bakımdan beta kriptoksantin'in vitamin E ve astaksantine göre daha fazla kardiyoprotektif etki gösterdiği sonucuna varılmıştır 34 . Miyokardiyal nekroz önlenmesine yönelik farklı bir çalışmada; C vitamininin nekroz oluşumunu %30'a kadar önlediği belirtilmiştir 9 . Wallert ve arkadaşları yaptıkları çalışmada E vitamininin miyokardiyal enfarktüs boyutunda azalmalara neden olduğu gösterilmiş ancak yüzde cinsinden oran verilmemiştir.…”
Section: İskemi-reperfüzyon Hasarında Vitaminlerin Etkinliğiunclassified
“…The mechanism underlying aortic occlusion-related tissue damage is not fully understood. Previous studies implicated reactive oxygen species (ROS)-mediated oxidative stress [ 3 , 4 , 6 , 7 ] . Several oxidant and antioxidant molecules and enzymes are involved in oxidative stress, the levels of which increase due to lipid peroxidation (LPO) [ 8 , 9 ] .…”
Section: Introductionmentioning
confidence: 99%